GENDER DIFFERENCES IN DEVELOPING OF COMPONENTS OF THE VOLITIVE SPHERE AT PRESCHOOLERS - Racu Jana; Mulico Iulia (Psihologie, 2019)
The article describes a comparative analysis of the development of volitive sphere at boys and girls of preschool age. The results of the level of concentration, volunteering, distribution in order to carry out action, activism, initiative and indepen dence, all these present gender differences, and consequently, boys surpass girls. These tendencies are particular during the whole preschool period of children.